Preparation and Property of Mo-Doped Visible-Light Response Titaniumdioxide Photocatalyst - Yingying Li; Xianliang Song; Zhedong Wei; Jianguang Zhang; Lijuan Qin; Shengying Ye (Journal of Spectroscopy)
Mo-titaniumdioxide (P25) photocatalyst with visible-light response was prepared with the ammonium molybdate for Mo source and titaniumdioxide for the raw materials by the method of dissolving and calcining. The photocatalysts’ structure was characterized by XRD, XPS, and UV-Vis absorption spectrum and TEM. The photocatalytic activities of Mo-titaniumdioxide were measured by the degradation of methylene blue (MB) under visible-light irradiation. The results showed that Mo characteristic peaks appeared at the point of 235.45 eV, 234.2 eV, 232.3 eV, and 231.1 eV. In Mo-titaniumdioxide crystal lattice, Mo6+ had the highest percentage (about 84.08%), indicating that Mo element was inserted into titaniumdioxide crystal lattice and considerable amount of Mo dopant was in the 6+ valence state, which restrained the recombination of electron-hole and had the visible-light photocatalytic activity. Photocatalytic degradation study indicated that the samples prepared at calcination temperature of 500°C were used to degrade MB; after 3 h, the degradation reached up to 80.67%.